Review on AI-Driven Health Care Field Post Covid-19 - Bhuvanagiri Mounish, Viswajeet Shankar Goswami (Mathematical Statistician and Engineering Applications, 2023)
Data has been a crucial part and everything is related to Data. Emerging technologies like AI, Machine Learning has proven their presence and has made significant developments. These technologies are utilized by many Health care providers and many other organizations. The orders for this operation involve various opinion and treatment recommendations, end-end activities related to the patient (involvement, Commitment, and Executive conditioning and can also be engaged in Laboratory and decision-making in specific conditions. AI can be Induced in ICUs, Diagnosing Assistance, Medication Assistance, Feedback collecting, and Blood reports while performing Surgeries. there are cases where AI can do healthcare tasks best when compared to humans